A brand new strategy of quantum relay strategy based on entanglement swapping - Min XU; Min NIE; Guang YANG; Changxing PEI (Dianxin kexue)
Quantum protocols based on entanglement are known as information security，reliability，flexibility and a broad prospect in use.Meanwhile，the fidelity of photons is also required.A new quantum relay strategy was proposed.By setting multi-relays between distant correspondents and under the assistance of classical communications，the strategy can execute entanglement swapping and entanglement purification to provide the correspondents with remote entanglement connection of stable fidelity.Performance analysis shows that by reasonable control of relay series，improvement of entanglement swapping and entanglement purification，the time delay and throughput can be significantly improved，necessary entanglement resources can be provided for the global quantum communication.